Psycho-social impact of malocclusion in patients seeking orthodontic treatment - Naik, Moode Kaladhar; Himabindua, M.; Vamsi, Kogila Jashva; Reddy, Boggula Rama Mohan (International Journal of Health Sciences, 2022)
Background: The present study was conducted for assessing Psycho-social effects of malocclusion in patients seeking orthodontic treatment. Materials & methods: 30 subjects seeking orthodontic treatment were enrolled in the present study. All the subjects were pre-informed about the study protocol. Study consisted of collection of information for psychosocial assessment using a questionnaire and clinical examination of malocclusion. Data regarding psychosocial impact of dental aesthetics was collected using a Psychosocial Impact of Dental Aesthetics Questionnaire. The responses were recorded by the examiner himself using the appropriate codes. All the oral examination procedures were carried out using sterile gloves, mouth mirror, tweezer and probe. Results: Out of the 30 children examined, there were 63.33% (19) males and 36.67% (19) females. The mean age of the subjects examined was 13.96 years. On the whole, the mean Dental self-confidence score differed significantly among both male and female children across the age groups. Overall, the mean social impact score did not differ significantly among both male and female subjects across the age groups. Conclusion: Dental aesthetics have a significant impact on the psychosocial aspects of human life.